Use of Social Media Among Health Sciences Students - Montoya Garces, Mariana (2023)
Social networks are continuous communication channels that impact both the sociocultural and educational spheres. In the realm of education, various pedagogical strategies are employed with the aim of reinforcing critical thinking, active participation, and autonomy in knowledge acquisition. Among the primary advantages of social networks, we encounter numerous sources of valuable information, which promote self-directed education on health-related topics. However, it is crucial to address disadvantages accurately, including the dissemination of misinformation and the handling of sensitive data. These connections between digital innovation and healthcare reflect a landscape fraught with challenges that demand precise exploration due to its rapid evolution. Databases such as PubMed, Scielo, ResearchGate, Elsevier, and Google Scholar were utilized to consult the initial bibliography published within the last 5 years, with the date range extending to the last 9 years.